2016
DOI: 10.1007/s12070-016-0986-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Indicators of Ossicular Necrosis in Tubotympanic CSOM

Abstract: Ossicular necrosis and erosion is commonly seen in CSOM with cholesteatoma but can also occur in tubotympanic CSOM. This usually comes as a surprise during surgery. Preoperative knowledge of ossicular necrosis helps the surgeon to be better prepared for the surgery and ossicular construction if required. Hence, this study is intended to identify the pre-operative indicators of ossicular necrosis. This cross sectional study was conducted in Father Muller Medical College in Mangalore. Sixty nine consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
2
13
2
Order By: Relevance
“…15 Adherence of perforation edges to the promontory also had significant association with ossicular necrosis (p <0.05) in the studies of Ebenezer J et al, Jayakumar CL and Srinivas et al studies. [10][11][12] Our finding was consistent with those studies. Jeng et al concluded that, adhesion causes confinement of inflammatory products and granulation tissue to a small blind sac causing hyperemia and increased pressure on ossicles leading to erosion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…15 Adherence of perforation edges to the promontory also had significant association with ossicular necrosis (p <0.05) in the studies of Ebenezer J et al, Jayakumar CL and Srinivas et al studies. [10][11][12] Our finding was consistent with those studies. Jeng et al concluded that, adhesion causes confinement of inflammatory products and granulation tissue to a small blind sac causing hyperemia and increased pressure on ossicles leading to erosion.…”
Section: Discussionsupporting
confidence: 92%
“…11 While Jayakumar CL et al noted ossicular necrosis in 23.1% cases (in 16 out of 69 patients) and incus was most commonly ossicle (62.5%) followed by malleus(31.2%) and then stapes (6.25%). 12 Srinivas et al noticed ossicular necrosis in only 11% cases (5 out of 47 patients). 13 Jeng et al also found ossicular necrosis in 11.1% (17 out of 153) patients of non-cholesteatomatous ears.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11,12 Our study is an exclusive study on female COM patients. Ginni et al observed patients of squamousal COM are mosly affected in 3 rd decade.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by several other authors where females have outnumbered males. [8][9][10][11][12] Most of the patients had bilateral disease (38.89%), followed by left ear as the only diseased ear. Bilateral affection may be due to the fact that the etiology or risk factors of CSOM are likely to affect both ears.…”
Section: Discussionmentioning
confidence: 99%